When Work And Family Are Allies: A Theory Of Work-Family Enrichment - Greenhaus, Jeffrey H.; Powell, Gary N. (Academy of Management Review, 2006)
We define work-family enrichment as the extent to which experiences in one role improve the quality of life in the other role. In this article we propose a theoretical model of work-family enrichment and offer a series of research propositions that reflect two paths to enrichment: an instrumental path and an affective path. We then examine the implications of the model for future research on the work-family enrichment process.